A conceptual literary exploration of Sayalan al-rahim (abnormal vaginal discharge) in Unani medicine: Saeedi R., Sultana A. *, Khan M.A., Farzana M.U.Z.N (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Unani literature is enriched with the concept of Sayalan al-rahim (abnormal vaginal discharge). It is the excessive abnormal vaginal discharge from the female genital tract and the commonest reason for which women seek medical attention. It adversely impacts reproductive health and contributes to significant morbidity. Therefore, a literary exploration in classical Unani literature for Sayalan al-rahim was searched to implement in the current era. Further, various search engines like PubMed, Medline, Google Scholar, Ovid, Science Direct, and Scopus were browsed for contemporary outlook of abnormal vaginal discharge with evidence-based medicine. According to various eminent Unani philosophers, Sayalan al-rahim is the disease that adversely affects the health of the women and should not be neglected; it can affect the fertility of a woman. The causes, clinical features, diagnosis, differential diagnosis and management of abnormal vaginal have been well-documented in the classical texts. Contemporary medicine discusses abnormal vaginal discharge as a symptom of female reproductive diseases. Few studies have been published related to Sayalan al-rahim caused due to various female reproductive tract infections. This literary research validates the Unani classical texts that are enriched with in-depth knowledge on abnormal vaginal discharge. Few evidence-based studies have proven that traditional Unani medicines are efficacious in abnormal vaginal discharge. Keywords: Abnormal vaginal discharge, Evidence-based studies, Sayalan al-rahim, Unani Medicine 1Department of Amraze Niswan wa Ilmul Qabalat (Gynecology and Obstetrics), Jamia Tibbiya Deoband, Saharanpur, U.P., India. 2Department of Amraze Niswan wa Ilmul Qabalat (Gynecology and Obstetrics), National Institute of Unani Medicine, Bengaluru, Karnataka, India. 3Department of Ilmul Jarahat (surgery), Jamia Tibbiya Deoband, Saharanpur, U.P., India. 4Unit of Amraze Niswan wa Ilmul Qabalat (Gynecology and Obstetrics), Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka *Correspondence: Sultana A., Associate Professor, Department of Amraze Niswan wa Ilmul Qabalat (Gynecology and Obstetrics), National Institute of Unani Medicine, Bengaluru, Karnataka, India. Email: drarshiya@yahoo.com, drasnium@gmail.com